Airbag application to passenger seat for aircraft: impact tests. Issue 3 (3rd May 2020) - Chiba, Masakatsu; Yasui, Takuya; Nambu, Yousuke; Katayama, Kazuo; Yutani, Hiroshi
Abstract: Impact tests were conducted for an airbag that was installed as an aircraft seat cushion to reduce the shock to passengers in the case of an emergency. A falling body was dropped against a pre-inflated test airbag which was equipped with an exhaust orifice. Acceleration and displacement of the falling body and the inner pressure of the test airbag were measured. The influences of diameter, length and rupture pressure of the exhaust orifice on the shock absorbability of the airbag were investigated.